PENERAPAN BALANCED SCORECARD SEBAGAI PENGUKUR KINERJA MANAJEMEN PADA RUMAH SAKIT UMUM DAERAH INDRAMAYU - Magdalena Nany; Lyna Raharjo; Kartika W.H (Jurnal Riset Akuntansi dan Keuangan, 2008)
The objective of this research was to measure management's performcmce by applying balanced scorecard. Balanced scorecard is a contemporary managernent tool used to upgrade organization's capability by multiplying financial performance. Balanced scorecard has 4 perspectives.These perspectives are financial perspective, customer perspective, process intern business perspective and learning and growth perspective. Data were collected by questionnaire and interview. Thirty 'five patients and 40 employees from District Hospital of Indrar4oyu were taken as samples. The results-obtainedfrom applytng balanced scorecardwere : (I) Financial perspective, ROI tends to increase, but revenae growth tends to decrease; (2) Customer perspective, patients'retention tends to decrease and patients' acquisition tends to increase, but patients do not satisfy enough with District Hospital of Indramayu; (3) Process intern business perspective, hospital's productivity tends to increase and profit margin tends to increase, to:o; (4) Learning and growth perspective, employees' productivity tends to increase, but employees' retenfion tends to increase and employees do not satisfu enough with District Hospital of Indramayu.Keywords: management's performance, balanced scorecard, financial perspective, customer perspective, process internbusiness perspective, learning and growth perspective.